The Albumin in Subarachnoid Hemorrhage (ALISAH) multicenter pilot clinical trial: safety and neurologic outcomes - Suarez, Jose I; Martin, Renee H; Calvillo, Eusebia; Dillon, Catherine; Bershad, Eric M; Macdonald, R Loch; Wong, John; Harbaugh, Robert (Stroke (1970), 2012)
Human albumin has been shown to exert neuroprotective effects in animal models of cerebral ischemia and humans with various intracranial pathologies. We investigated the safety and tolerability of 25% human albumin in patients with subarachnoid hemorrhage. The Albumin in Subarachnoid Hemorrhage (ALISAH) Pilot Clinical Trial was an open-label, dose-escalation study. We intended to study 4 different dosages of albumin of increasing magnitude (0.625 g/kg: Tier 1; 1.25 g/kg: Tier 2; 1.875 g/kg: Tier 3; and 2.5 g/kg: Tier 4). Each dosage was to be given to 20 adult patients. Treatment was administered daily for 7 days. We investigated the maximum tolerated dose of albumin based on the rate of severe-to-life-threatening heart failure and anaphylactic reaction and functional outcome at 3 months. We treated 47 adult subjects: 20 in Tier 1; 20 in Tier 2; and 7 in Tier 3. We found that doses ranging up to 1.25 g/kg/day×7 days were tolerated by patients without major dose-limiting complications. We also found that outcomes trended toward better responses in those subjects enrolled in Tier 2 compared with Tier 1 (OR, 3.0513; CI, 0.6586-14.1367) and with the International Intraoperative Hypothermia for Aneurysm Surgery Trial cohort (OR, 3.1462; CI, 0.9158-10.8089). Albumin in doses ranging up to 1.25 g/kg/day×7 days was tolerated by patients with subarachnoid hemorrhage without major complications and may be neuroprotective. Based on these results, planning of the ALISAH II, a Phase III, randomized, placebo-controlled trial to test the efficacy of albumin, is underway. URL: http://clinicaltrials.gov. Unique identifier: NCT00283400.